Evaluation of an assessment scale for aesthetic outcome in breast reconstructions based on digital photos in both 2D and 3D format. Issue 1 (28th February 2023) - Tallroth, Linda; Mobargha, Nathalie; Velander, Patrik; Klasson, Stina; Becker, Magnus
Abstract: The aesthetic outcome is crucial in a breast reconstruction. Our aim was to evaluate the intra- and interrater reliability of an aesthetic outcome assessment scale with digital photos of breast reconstructions in two-dimensional (2D) and three-dimensional (3D) format. Thirty-three women with delayed breast reconstructions, consecutively participating in a five-year follow-up between November 2019 and June 2021, were included in the study. Of these, 14 were reconstructed with an expander prosthesis (EP) and 19 with a deep inferior epigastric perforator (DIEP) flap. Photos of the breasts were assessed in 2D and 3D format by expert, layman and patient panels. Data were analysed with the weighted kappa (wk) statistics. The intrarater agreements were moderate to substantial, with wk between 0.66 and 0.73 for the panels. Within the panels, the interrater agreements were 0.46–0.62. Moderate agreements were found between the matched 2D and 3D format photos (wk 0.62–0.66). The patient panel graded scar appearance worse in 3D compared with 2D format. In all panels, there was a tendency towards DIEP flap reconstructions receiving higher aesthetic outcome grades compared with EP. Thus, the aesthetic outcome assessment scale demonstrated acceptable agreements between the individual panellists and within the panels. Scars captured in 3D format may provide a greater resemblance to the reality compared with 2D. Implications for clinics remain to be further studied.